Implementasi Kurikulum Merdeka di SMK Negeri 2 Bukittinggi - Zahrah, Ayumi; Gistituati, Nurhizrah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to find out the implementation of the independent curriculum at SMK Negeri 2 Bukittinggi. The research method used is qualitative descriptive with data collection using observation, interviews, and documentation. The informants in this study consisted of school principals, curriculum representatives, facilities and infrastructure representatives, teachers and students. Data analysis is carried out qualitatively with the stages of data reduction, data presentation and conclusion drawing. The results of the study show that the implementation of the independent curriculum at SMK Negeri 2 Bukittinggi is carried out in three stages, namely (a) Learning planning is carried out in several activities, namely forming a special team of subject teachers, analyzing learning outcomes, formulating learning objectives, compiling the flow of learning objectives, compiling teaching modules, and planning P5; (b) The implementation of learning consists of preliminary activities, core activities, and closing activities; (c) Assessment of learning using formative assessment and summative assessment. Factors that support the implementation of the independent curriculum at SMK Negeri 2 Bukittinggi are the principal, teacher competence, student activity, commitment from school residents, facilities and infrastructure. Meanwhile, the factors that hinder the implementation of the independent curriculum at SMK Negeri 2 Bukittinggi are teachers' understanding of the concept of the independent curriculum that is not yet complete, limited time in implementing differentiated learning and student learning readiness